2023
DOI: 10.1002/jbmr.4770
|View full text |Cite
|
Sign up to set email alerts
|

Bmi‐1 Overexpression Improves Sarcopenia Induced by 1,25(OH)2D3 Deficiency and Downregulates GATA4‐Dependent Rela Transcription

Abstract: Sarcopenia increases with age, and an underlying mechanism needs to be determined to help with designing more effective treatments. This study aimed to determine whether 1,25(OH)2D3 deficiency could cause cellular senescence and a senescence‐associated secretory phenotype (SASP) in skeletal muscle cells to induce sarcopenia, whether GATA4 could be upregulated by 1,25(OH)2D3 deficiency to promote SASP, and whether Bmi‐1 reduces the expression of GATA4 and GATA4‐dependent SASP induced by 1,25(OH)2D3 deficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This can affect the function of neighboring cells and tissues, promoting tissue inflammation and deficiency, which could cause cellular senescence. Studies revealed that 1,25(OH)2D3 deficiency could cause cellular senescence and SASP in skeletal muscle cells to induce sarcopenia [17]. The innate DNA sensing pathway is essential to regulating SASP and senescence [18].…”
Section: Introductionmentioning
confidence: 99%
“…This can affect the function of neighboring cells and tissues, promoting tissue inflammation and deficiency, which could cause cellular senescence. Studies revealed that 1,25(OH)2D3 deficiency could cause cellular senescence and SASP in skeletal muscle cells to induce sarcopenia [17]. The innate DNA sensing pathway is essential to regulating SASP and senescence [18].…”
Section: Introductionmentioning
confidence: 99%